PEMUNGUTAN PAJAK SARANG BURUNG WALET DI KABUPATEN TABALONG - Nurmila Sari; Rusniati (Universitas Lambung Mangkurat, 2020)
This study aims to determine every process in the collection of bird's nest tax and to find out how the development of swallow's nest tax income in Tabalong Regency. This research will start from finding out the development of bird nest tax revenue and income in 2018-2019. In the collection of waIet's nest tax funds there are registration, data collection, determination, and billing. In 2018 the income from waIet's nest tax was 38.15%, but in 2019 it decreased by 22.39%.